Russian and British "new drama" of the turn of the 21st century: General concepts, meanings, and performances - Kislova, Larisa S. (Имагология и компаративистика)
At the turn of the 21st century, Russian “new drama” manifests the British playwright tradition (mainly of the British Royal Court Theater). Choosing the most relevant themes, Russian and British playwrights strive not just to shock and challenge the audience with the cruelty of what is happening on the stage, but to make the reader/viewer tackle the problems, understand the characters who are often imperfect and marginalized humans. These texts form a single artistic space that integrates various shades of pain, fear, and suffering having no geographical, political, social, and humanitarian borders. Thus, destroying the criteria of rationality, demonstrating the infinite nightmare of everyday life, the British and Russian playwrights make some international project. After the rise that characterized the British theater in the 1950s and 1960s, there came a period of some passive interest to the theater culture in the 1970s and 1980s. Yet, at the turn of the 21st century, a new generation of playwrights came to literature. Mark Ravenhill (1966), Sarah Kane (1971– 1999), Anthony Neilson (1967), Philip Ridley (1964), Martin McDonagh (1970), Joe Penhall (1967) manifested the artistic principles of the so-called “angry young people” and the traditions of Antonin Artaud’s “Theatre of Cruelty”. Antonin Artaud saw the possibility of human liberation by magnifying cruelty and placing it in the foreground in the existing picture of the world. Freedom of choice and complete disregard for morality and traditional values lead to violence, and a person becomes a professional buyer or seller, a victim or an executioner. In the world where the main purpose of life is buying and selling, a person lives according to the laws of free market and can be both a buyer and a commodity. Human cruelty is determined by the desire to humiliate others, which can lead to serious consequences. The central theme of Mark Ravenhill’s drama is the idea of consumerism – a distorted value system that has become dominant in a consumer society with a pronounced market philosophy. In the universe of infinite buying and selling, even events related to the death of people turn into commodity. As for the Russian “new drama” with its everyday nightmares and “communicative violence” (the term introduced by Mark Lipovetsky), we rather mean an artistic phenomenon that is characteristic of the global social and cultural situation at the turn of the millennium – the period of destructing one society and creating another. The Russian audience has never been jaded, cynical, and bored. Thus, rather offensive and unjustifiably cruel drama images perform the primary function of depicting the surrounding reality, which has become too familiar, and therefore often not properly realized. Consequently, the Russian playwrights of the turn of the 21st century aim to make the person with locked consciousness, the one, who tries not to notice the horrors of reality, “look back in anger”.